Supply Chain Management & RFID: an Analysis of Research Productivity - Shrivastava, Divya Prakash; Kumar, Anil (International Journal of Supply Chain Management, 2019)
Radio frequency identification (RFID) Supply chain management (SCM) are an integral part of today's business world. RFID increases productivity and convenience. There are several studies conducted in the past to examine the question of productivity of the authors. However, prior studies have not discussed in detail the research productivity patterns of individual RFID SCM authors together, across a relatively large number of journals and a lengthy time frame. Previous studies have also not established any benchmark of individual research productivity, regarding both the number of publications, i.e. quantity and the impact of those published papers, i.e. quality, required to place among the leading contributors in the field of RFID SCM collectively. The present study examined 631 global publications on "RFID Supply Chain Management" downloaded from Scopus database during 1999-2015. The positioning and associated percentiles of individual authors were calculated and prepared six quality and quantity metrics from equal credit method and direct count method; authors identify the aggregate productivity standards necessary for an individual author to be ranked at various places in the field of RFID SCM together.